Determinants of Profitability of Indian Commercial Banks - Jain, Ravi Kumar; Metri, Bhimaraya; Rao, K. P. Venugopala (Indian Journal of Finance, 2019)
This study examined the effect of determinants influencing the performance of 45 commercial banks in India, post the global financial crisis. The random effect model on balanced panel data for the period from 2010 - 2016 was performed to determine the impact of the macroeconomic and bank specific factors on the profitability of 45 Indian commercial banks (26 public sector banks and 19 private sector banks). The results suggested that the private sector banks performed better than the public sector banks. Findings of the model revealed that a significant part of the commercial banks' profitability was explained by bank specific factors like the NPAs, profit per employee, operating profit to total assets, and investment to total assets, while the capital adequacy ratio remained insignificant. The macroeconomic variables like GDP, IIP, and WPI were significant in explaining the profitability of the Indian commercial banks. This paper highlighted new facts in better understanding of the profitability of commercial banks in growing economies like India.